The Influence of Work-Family Conflict and Motivation on The Performance of Female Employees - Munawi, Ahmad Syarif; Nurhasan, Rohimat; Rismanto, Hilman (Fakultas Ekonomi Universitas Garut, 2023)
Work-Family Conflict or WFC describes that there is a misalignment between the roles of individuals in the family and at work, so this can affect the balance of work life and personal life. On the other hand, motivation is one of the things that affects employees' desire and effort to achieve organizational goals. This research intends to analyze the impact of WFC and motivation on female employees' performance. This research method uses a quantitative approach using questionnaires distributed to female employees at PT Changshin Reksa Jaya Garut. The collected data then analyzed using structural equation model method to test the influence on WFC and motivation on employee performance at PT Changshin Reksa Jaya Garut. The results showed that WFC has a significant negative influence on the performance of female employees. This conflict can cause stress, burnout, and job dissatisfaction that negatively affect employee productivity and performance. In addition, motivation has a significant positive influence on the performance of female employees. Motivated employees tend to have higher levels of performance because they have an internal drive to achieve goals and high standards of work.